Feeling mad - Holmes, Kirsty (New York KidHaven Publishing, 2019)
Learn about healthy ways to deal with feelings of anger. Nonfiction picture book featuring the character Raging Raccoon focuses on what causes anger and how to properly approach dealing with those feelings
Education
1 2 13
Keywords: Anger in children -- Juvenile literature; Emotions -- Juvenile literature